2016
DOI: 10.1093/jac/dkw109
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic substitution E157Q in HIV-1 integrase increases R263K-mediated dolutegravir resistance and decreases DNA binding activity

Abstract: This study shows that E157Q may act as a compensatory mutation for R263K. Since E157Q is a natural polymorphism present in 1%-10% of HIV-positive individuals, it may be of particular importance for patients receiving INSTI therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 23 publications
(33 reference statements)
2
24
0
Order By: Relevance
“…Whether this situation persists or whether a few individuals who are infected with viruses that can develop de novo resistance against this drug will eventually be identified is the subject of anxious scrutiny. An eventual de novo virological failure with resistance mutations may derive from preexisting rare polymorphisms, including E157Q and others (23, 24). In any case, to date, DTG has demonstrated an exceptional robustness against the emergence of drug resistance mutations in treatment-naive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this situation persists or whether a few individuals who are infected with viruses that can develop de novo resistance against this drug will eventually be identified is the subject of anxious scrutiny. An eventual de novo virological failure with resistance mutations may derive from preexisting rare polymorphisms, including E157Q and others (23, 24). In any case, to date, DTG has demonstrated an exceptional robustness against the emergence of drug resistance mutations in treatment-naive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, rare DTG failures are often associated with the R263K substitution, whereas RAL and EVG select for classical resistance mutations, including mutations at positions G140 plus Q148 or the N155H mutation. We previously reported that the R263K mutation may in large part be incompatible with classical resistance mutations for reasons of decreased replicative fitness and low-level resistance (32)(33)(34). Whether the resistance levels of mutants combining the R263K mutation with classical resistance mutations are also susceptible to acetylation inhibition remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation is under way to pinpoint the exact cause of our observed results through use of mass spectrometry analysis and the study of IN-DNA interactions by use of multiple C-terminal mutants. We also previously reported an effect of the R263K substitution on IN DNA binding activity in cell-free assays (11,32). While this may also be considered a mechanism through which the substitution provides resistance, it is important that these studies were performed with recombinant enzymes purified from Escherichia coli that most likely lack proper posttranslational modifications (37).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported in a patient with virological failure on a DTG-containing regimen [28]. It appears to reduce RAL and EVG susceptibility by 2-to 3-fold [29,30] and to increase DTG susceptibility [31]. Seven (13.2%) patients had the HIV-1 integrase mutation L74I or L74M detected in 4 different HIV-1 subtypes, 3 in A1, 1 in B, 2 in C, and 1 in CRF02_AG.…”
Section: Discussionmentioning
confidence: 77%